Microvascular perfusion MRI improves therapy monitoring and detects early recurrences of gliomas: a large-scale trial of 2000 follow-up examinations - Stadlbauer, Andreas; Nikolic, Katarina; Marhold, Franz; Doerfler, Arnd; Kinfe, Thomas M.; Meyer-Bäse, Anke; Schnell, Oliver; Ökrösi, Alexandra; Heinz, Gertraud; Oberndorfer, Stefan (American journal of neuroradiology, 2025)
BACKGROUND AND PURPOSE: Detecting glioma recurrence is fundamental for clinical patient outcomes; however, conventional MRI (cMRI) techniques may be limited, leading to diagnostic uncertainty relevant for therapeutic intervention. This study aimed to evaluate whether a microvascular perfusion (µPerf) imaging technique based on spin-echo DSC perfusion MRI could support the early detection of glioma recurrence compared with cMRI by characterizing subtle vascular changes preceding macroscopic tumor growth. - MATERIALS AND METHODS: A total of 351 patients with gliomas who underwent 2003 follow-up MRI examinations were retrospectively evaluated, with 422 of these examinations subjected to detailed quantitative analysis. The standard cMRI protocol was extended by applying the µPerf approach, with an additional 2 minutes for data acquisition. Custom-made Matlab software was used to generate imaging biomarker maps for microvascular CBV and microvascular type indicator. The clinical utility of µPerf was assessed by comparing its findings with radiologic interpretations of cMRI data, which were reviewed in consensus by at least 2 board-certified radiologists. Statistical analyses included the calculation of diagnostic performance metrics and the area under the receiver operating characteristic curve (AUROC) to evaluate glioma recurrence detection. - RESULTS: The µPerf technique exhibited superior diagnostic performance, achieving an accuracy of 97.4% and AUROC values of 0.987 (95% CI, 0.976-0.999) for microvascular type indicator and 0.982 (95% CI, 0.965-0.998) for microvascular CBV, significantly surpassing cMRI (accuracy: 85.1%; AUROC: 0.941; 95% CI, 0.918-0.965 for CBV). µPerf identified glioma recurrence earlier than cMRI in 13.5% of cases, with the time interval ranging from 41 to 353 days (mean, 137 days). During this time, tumor volume increased by 38% to as much as 155-fold (mean, 9.1-fold). Notably, early recurrences of high-grade malignant gliomas were predominantly characterized by microvascular changes compared with later-stage recurrences. - CONCLUSIONS: µPerf improves early detection of glioma recurrence and shows a higher sensitivity of microvascular changes compared with cMRI. µPerf has significant potential to promote more timely and personalized treatment strategies, which, in turn, could improve patient outcomes. Notably, µPerf works with standard clinical follow-up protocols, but its integration into clinical practice requires further validation through multicenter studies and long-term outcome analyses.
Gesehen am 20.01.2026